(untitled) (Research, Society and Development, 2021)
Data related to postoperative infection in surgically-assisted rapid maxillary expansion (SARME) are scarce. Our goal was to compare the effects of two different prophylactic antibiotic regimens on infection rates in patients undergoing SARME. A randomized, double-blind clinical trial was carried out with 23 patients (06 men and 17 women) who received 1g cefazolin one hour before the procedure (Group 1 – G1) or 1g cefazolin one hour before the procedure and again in the first 24 postoperative hours (Group 2 – G2). Patients were followed up for one month after surgery. Pain was greater in G1 with a statistically significant difference in the follow-ups of 1, 2, 7 and 21 postoperative days (p<0.05). Variable such as edema, erythema, fever, abscess and drainage did not differ between groups. Despite the similarities between the groups, the total sum of inflammatory events was 17 times higher in G1 (p<0,001). A single dose of cefazolin 1g one hour before the procedure is sufficient to prevent infection in patients undergoing SARME. These findings may help to decrease the indiscriminate use of antibiotics in in these situations, thus preventing the emergence of bacterial resistance and complications associated with the use of antibiotics.